What is the evidence-base for climate-smart agriculture in Tanzania? - Lamanna, Christine; Kimaro, Anthony A.; Arslan, Aslihan; Corner-Dolloff, Caitlin; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Evidence exists to support CSA programming on the most widely cultivated crops (e.g. maize), and most common agricultural practices (e.g. fertilizer addition) in Tanzania. However, products and places central to rural livelihoods such as livestock, coastal drylands, and humid regions near Lake Victoria are understudied. Data on how CSA changes agricultural productivity is widely available (77% of the data), while 20% of the data is related to resilience indicators, and only 3% deals with greenhouse gas mitigation outcomes. Practitioners should draw on this rich evidence base for CSA in Tanzania, while also prioritizing the generation of evidence for understudied products, agroecologies, and practices.